E-047 Novel treatment of isolated P1 segment "blister" aneurysm with telescoping stents. (4th July 2012) - Chang, T; Bourgeois, A; Kvamme, P
Abstract : Purpose: Dissecting posterior cerebral artery aneurysms are rare lesions that pose difficult treatment options. The purpose of this case is to describe the complications of stenting of a posterior cerebral artery dissecting aneurysm, novel treatment of this complication, and outcomes. Materials and Methods: Case report and retrospective chart review of a 34-year-old female who was transferred to our institution from an outside hospital with a history of subarachnoid hemorrhage. Patient underwent endovascular stenting of a dissecting aneurysm of the P1 segment of the left posterior cerebral artery after the aneurysm failed to improve after 3 months of observation. Results: Following flow modulation therapy consisting of three Enterprise Vascular Reconstruction devices placed across the aneurysm, initial post treatment angiogram showed excellent modulation of flow within the aneurysm. Patient represented 10 days later with nausea, slurred speech and gait disturbance. CTA showed narrowing of the right P1 segment with possible flow limiting stenosis. MRI showed a new right sided pontine infarct. Patient was treated with Heparin, Angiomax infusion, Rheopro infusion, asparin, and plavix. Symptoms resolved after 1 day of anticoagulation/thrombolytic therapy. Follow-up angiogram showed significant morphologic change at the posterior cerebral artery with straightening of the posterior cerebral artery and kinking of the basilar artery. Our belief is that the radial forces created by the use of multiple stents caused the morphologic changes to the basilar artery and posterior cerebral artery. This morphologic change then damaged the small perforating vessels arising from the basilar artery and resulted in a pontine infarct. Two-year clinical follow-up revealed no persistent neurologic defects with return of the patient to her baseline functional status. Conclusion: Flow modulation therapy of a dissecting posterior cerebral artery aneurysm by stenting is a valid treatment option. Care must be taken when determining the location and number of stents to be used as increasing radial forces can result in morphologic alteration of the native vessels and, as in this case, infarct. While this patient experienced no lasting deficits, infarcts in this vascular distribution could have the potential for catastrophic effects. Competing interests: None.